Early failures and further re-interventions of direct posterior restorations at Public Dental Service 15-year retrospective observation - Palotie, Ulla; Tseveenjav, Battsetseg; Vehkalahti, Miira M. (Elsevier, 2026)
Objectives
The aim of this register-based retrospective study was to evaluate the reasons recorded for early failures of direct posterior restorations involving two or three surfaces with extension occlusally, and to follow up the fate of these teeth after replacement or repair over 15 years.
Methods
Subjects were selected based on information from electronic patient files of 25- to 30-year-old patients with posterior restorations, either primary or re-restorations, performed in 2002 at the Helsinki City Public Dental Service (PDS). Patients with early failures, defined as any intervention procedure within the subsequent year after the 2002 restoration, were included (N = 331). Treatment procedures, both early failures and during follow-up, were grouped as restorations, endodontic treatments/retreatments, or extractions.
Results
Caries was the reason for re-intervention in 15.7 % of early failures, while poor restoration, e.g. fracture or poor restoration anatomy, was reported in 28.7 %, pain or emergency in 30.5 %, and reason not specified in 25.1 %. Linear regression model revealed that accumulation of further failures was associated with whether the tooth had a primary intervention or re-restoration (p < 0.003) as well as the patient having fewer than 28 teeth (p < 0.001) and none healthy CPI sextants (p < 0.035). Following the re-interventions, 75 % of the teeth survived over a 15-year period.
Conclusions
Within this study’s limitations, we found that pain and restoration deficiencies were the main reasons for re-intervention within one year in a selected Helsinki City PDS patient group. Re-interventions were more frequent in previously restored teeth and were generally successful in preserving most teeth, even those with large composite restorations.